Judging 'Privileged' Jews : Holocaust Ethics, Representation, and the 'Grey Zone' - Brown, Adam 1952- (War & Genocide, 2013)
The Nazis’ persecution of the Jews during the Holocaust included the creation of prisoner hierarchies that forced victims to cooperate with their persecutors. Many in the camps and ghettos came to hold so-called “privileged” positions, and their behavior has often been judged as self-serving and harmful to fellow inmates. Such controversial figures constitute an intrinsically important, frequently misunderstood, and often taboo aspect of the Holocaust. Drawing on Primo Levi’s concept of the “grey zone,” this study analyzes the passing of moral judgment on “privileged” Jews as represented by writers, such as Raul Hilberg, and in films, including Claude Lanzmann’s Shoah and Steven Spielberg’s Schindler’s List. Negotiating the problems and potentialities of “representing the unrepresentable,” this book engages with issues that are fundamental to present-day attempts to understand the Holocaust and deeply relevant to reflections on human nature